Islamic Parenting in Education of Children's Conduct in The Digital Era - Eka Nur Laili Shofi Zuni (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
This study uses a qualitative approach with a descriptive qualitative type. Data collection techniques using observation, interviews, and documents. The data were analyzed from preparing data, coding data, descriptions and themes, reporting findings. The results of this study indicate the challenges of Islamic parenting in educating children's morals in the digital era, namely children who are smarter than their parents, children who are lazy to move, and children who are always connected to cellphones. In dealing with these challenges, parents seek to be digitally literate, introduce the concept of morality, and build morals by building and controlling children's interactions. The efforts of parents in educating children's morals in the digital era by providing advice, attention, educating with targhib and tarhib, participating in parenting activities at school, sharing with parents whose children excel in school, and filling out liaison books.